Effect of ambient temperature and water content on emulsified heavy fuel oil droplets evaporation: Evaporation enhancement by droplet puffing and micro-explosion. (15th February 2023) - Chen, Xiaoyu; Xi, Xi; Xiao, Ge; Zhang, Lenan; Wang, Zixin; Long, Wuqiang
Graphical abstract: Highlights: The evaporation of emulsified HFO droplet is divided into three phases. The heat equilibrium sub-phase is the distinguishing feature of emulsified HFO. The first two phases can be prolonged with the increase of water content. Compared with HFO the evaporation of emulsified HFO is promoted significantly. The duration of fluctuation evaporation phase is decisive for droplet lifetime. Abstract: In this study, the evaporation characteristics of emulsified heavy fuel oil (HFO) with water content from 0 to 30 % at the ambient temperatures of 673, 773, and 873 K are experimentally studied. Three distinguishing phases can be clarified and summarized, including initial heating, fluctuation evaporation, and steady evaporation phases. The fluctuation evaporation phase involves the two sub-phases of heat equilibrium and secondary heating, which are first discovered in the evaporation of emulsified HFO. And the heat equilibrium sub-phase is the distinguishing feature of emulsified HFO from other blended fuels. The duration of the initial heating phase and the fluctuation evaporation phase decreases with the elevated ambient temperature but increases with rising water content. However, the variation of micro-explosion intensity with ambient temperature and water content is the opposite. The time consumed in the fluctuation evaporation phase determines the droplet lifetime. The difference between the evaporation characteristics of HFO and emulsified HFO is that the fluctuation evaporation phase of HFO is not distinct, which is due to the violent and frequent micro-explosion occurring in the emulsified HFO droplet. Consequently, the droplet lifetime of emulsified HFO is significantly shorter than that of HFO. Eventually, a regression formula for the dependences of droplet lifetime from temperature and water content is proposed, which can provide a reference for the practical application of emulsified HFO.